Development Trends and Suggestions of Nucleic Acid Vaccines - Li Aihua (《中国工程科学》杂志社, 2021)
Considering the urgent needs of coronavirus disease 2019 (COVID-19) epidemic prevention and control, nucleic acid vaccine has attracted great attention in the vaccine research and development (R&D) field owing to its high efficiency and good efficacy. Particularly, the R&D process of messenger RNA (mRNA) vaccine has significantly accelerated, and the mRNA vaccine was approved for the first time to be marketed and used in humans. This article first summarizes the R&D status of nucleic acid vaccines from the aspects of related technical concept, R&D path, and development trend, and identifies the characteristics of nucleic acid vaccines. Subsequently, it analyzes the impact of COVID-19 outbreak on the mRNA vaccine research, summarizes the main fields of application of nucleic acid vaccines, and studies the possible technical and safety problems. Furthermore, we suggest that the key technologies of nucleic acid vaccines should be developed by improving the target gene expression, delivery system, immune response, and mRNA stability and storage. Moreover, the safety and efficacy of nucleic acid vaccines should be strictly monitored; stakeholders should conduct research on mRNA vaccine technologies that have safety risks and potentially disruptive effects on cancer and infectious disease prevention and control; and a forward-looking technological layout and technical transformation should be emphasized.